Rewarding the social benefits of small-scale farming - Abate, Gashaw T.; Baye, Kaleab; Bernard, Tanguy; Chamberlin, Jordan; Hill, Ruth Vargas; Moussadek, Rachid; Senghor, Lamine (CGIAR System Organization, 2025)
Small-scale farmers are often encouraged to adopt innovations that generate significant social benefits, including improved nutrition, food safety, and environmental sustainability, yet market mechanisms frequently fail to reward these contributions. Adoption of such socially desirable practices remains below the social optimum due to unobservable attributes, high verification costs, limited production scale, and misaligned private incentives. We propose a simple framework that highlights four key dimensions influencing adoption: returns to farmers (R), adoption costs (C), inspection costs (I), and transaction scale (Q). Interventions can target these dimensions individually or in combination, such as reducing verification costs, aggregating production, subsidizing adoption, or enhancing market premiums. We illustrate this framework through three case studies: aflatoxin mitigation, biofortified crop adoption, and conservation agriculture, demonstrating how technology, policy, and market-based instruments can be coordinated to incentivize the adoption of socially beneficial innovations and practices. Our analysis emphasizes the importance of multidisciplinary approaches, integrated public and private actions, and dynamic interventions that account for both immediate and long-term social returns. By explicitly connecting adoption incentives with verification and market constraints, the framework guides research and policy toward more effective strategies to reward smallholders for their contributions to public goods and sustainable development.